Liposarcoma miRNA signatures identified from genome-wide miRNA expression profiling. (June 2014) - Zhou, Yuhong; Zhang, Yong; Huang, Yuan; Tan, Ruoying; Liu, Tianshu; Zhuang, Rongyuan; Zhu, Miaojun; Han, Wumei; Hou, Yingyong; Liu, Ju; Zhang, Li; Jiang, Yaping; et al.
ABSTRACT: : Aims: To identify the miRNA expression profile of liposarcoma (LPS) that could facilitate detection of LPS, and provide the basis for further investigation of molecular-targeted therapeutic drugs.Materials & methods: A real-time quantitative PCR assay was performed to analyze the expression of 1888 miRNAs from 25 LPS tumor tissue samples, 16 samples of adipose tissue adjacent to the tumors and 18 normal adipose tissue samples from patients with LPS.Results: Ten dysregulated miRNAs were identified that effectively distinguished LPS tissue from adipose tissue and benign lipoma tissue, and LPS tumor tissues from normal adipose tissues in LPS patients. Furthermore, the expression profiles of miRNAs could also classify the subtype of LPS.Conclusion: The identified miRNAs appear to be novel biomarkers for the detection of LPS, and may contribute to an understanding of the mechanisms of LPS tumorigenesis and its development, and further elucidate the characteristics of LPS subtypes.